Ortho‐Functionalization of Benzimidates and Benzamidines. Issue 12 (23rd March 2022) - Borah, Gongutri; Dam, Binoyargha; Patel, Bhisma K.
Abstract: In recent years, benzimidates and benzamidines have received tremendous importance as starting materials owing to their electronic properties and high reactivity. Their application as directing groups for constructing biologically active molecules has been a hot topic of discussion. Because of the presence of nucleophilic nitrogen in both these moieties, they can easily provide a co‐ordinating site to catalysts to form metallocyclic complexes which activate the inert Csp 2 −H bond thereby producing desired N‐ heterocycles. In this review, we have summarized the developments in ortho ‐functionalization of benzimidates and benzamidines using several coupling partners. Reaction mechanisms of protocols, their substrate versatility and limitations of those procedures along with their uses have also been addressed. Abstract : In recent years, benzimidates and benzamidines have received tremendous importance as starting materials owing to their electronic properties and high reactivity. Their application as directing groups for constructing biologically active molecules has been a hot topic of discussion. This encyclopaedic review demonstrates latest unearthing of the emerging ortho ‐functionalization of benzimidates and benzamidines in organic synthesis. Reaction mechanisms of protocols, their substrate versatility and their uses have also been addressed.